Rancang Bangun Mesin Destilator Pengubah Limbah Plastik Menjadi Minyak - Pandam Eko Prihatmoyo; Denny Dermawan; Fipka Bisono (Proceedings Conference On Design Manufacture Engineering And Its Application, 2018)
Plastic is a human need in everyday life, one of which is as a place to wrap food and drinks. The increasing level of public consumption, the more plastic waste produced. Waste from plastic is very difficult to decompose naturally. In order to overcome this, of course, we need a way to process the plastic waste into more useful things and also have benefits for the community, one way is to recycle plastic waste into fuel, which is fuel in the form of oil. But in making a new innovation, a tool is needed that can transform a waste into something that is beneficial to society in general. One of them is by distillation or distillation. A tool used to separate chemicals based on differences in speed or ease of evaporation or volatility of materials. In this distillation, the mixture of the ingredients boils so that it evaporates and the steam is then boiled back into liquid form. Substances that have a lower boiling point will evaporate first. Later this steam will turn into oil using the help of a condenser. Where the steam entering the condenser will condense and form water grains. Which will later turn into oil. The oil produced through this distillation process with PET and PP plastic as much as 500 ml for 5 kg of plastic.